PENGARUH AKUNTABILITAS, SKEPTISME PROFESIONAL, KOMPETENSI AUDITOR, DAN E-AUDIT TERHADAP KUALITAS HASIL AUDIT PADA KANTOR INSPEKTORAT DAERAH KOTA MAKASSAR - Hilman, Nurfadhilah; Laekkeng, Mursalim; Amiruddin, Amiruddin (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
This study aims to examine and analyze the effect of accountability, professional skepticism, auditor competence and e-audit on the quality of audit results at the Makassar City Regional Inspectorate Office. The hypothesis of this study is that accountability, professional skepticism, auditor competence and e-audit have a positive and significant effect on the quality of audit results at the Makassar City Regional Inspectorate Office. The data used in this study are primary data in the form of respondent's assessment of accountability, professional skepticism, auditor competence, e-audit, and quality of audit results at the Makassar City Regional Inspectorate Office, with a population of 35 auditors and a sample of 31 auditors. Methods of data collection using questionnaires and literature study. The data analysis technique used multiple linear regression analysis, t test, F test and coefficient of determination test. The results showed that: (1) accountability had a positive and significant effect on the quality of audit results at the Makassar City Regional Inspectorate Office; (2) professional skepticism had a positive and significant effect on the quality of audit results at the Makassar City Regional Inspectorate Office; (3) auditor competence has a positive and insignificant effect on the quality of audit results at the Makassar City Regional Inspectorate Office; and (4) e-audit had a positive and significant effect on the quality of audit results at the Makassar City Regional Inspectorate Office. This means that auditor accountability, auditor professional skepticism, and e-audit can support the improvement of the quality of audit results.Keyword: Accountability, Professional Skepticism, Auditor Competence, E-Audit and Quality of Audit Results